Relationship between Risk Committee Existence and Financial Performance of Commercial Banks in Kenya - Raymond Kipyegon Kemboi; Isaac Kiprotich Naibei; Peter Kipkosgei Sirmah; Peter Kimutai Cheruiyot (International Journal of Engineering and Management Research, 2019)
Performance of some banks in Kenya has been declining leading to their collapse or receivership. This may be attributed to many factors such as risk exposure. In bid to protect the financial sector, Central Bank of Kenya therefore directed all the banks to manage risks. One of the mechanisms used by the banks to manage risks is risk committee. Some banks established risk committees while others did not. There is limited knowledge on the relationship between this risks committee and financial performance in commercial banks. This study therefore aimed at determining the relationship between risk committee existence and financial performance of commercial banks. The target population was all commercial banks operating in Kenya. The study adopted longitudinal research design that covered a period of five years (2013- 2017). The study used secondary data extracted from annual consolidated and financial reports. Information on specific financial performance indicator was RoA (return on assets) and risk committee existence was extracted from annual reports. Data was analyzed using SPSS by way of regression analysis. The study found that there is a significant positive relationship between risk committee existence and financial performance where the coefficient was r=0.299. The results showed that the model explained 9% (R2 = 0.09, Adjusted R2= 0.1084, F (1) = 17.301, p=0.000, p˂0.05). This shows that 9 percent in the variations of RoA can be explained by risk committee existence. From the results, it is evident that risk committee existence and RoA have a significant positive relationship. The study recommends that commercial banks should fully implement risk committees in their operations. This will help the commercial banks to manage risk exposure and improve their financial performance.